AM-FM texture image analysis in brain white matter lesions in the progression of multiple sclerosis - Loizou, Christos P.; Murray, Víctor; Pattichis, Marios S.; Pantziaris, Marios; Pattichis, Constantinos S. (My University, 2010)
We present the use of multiscale Amplitude Modulation Frequency Modulation (AM-FM) methods for analyzing brain white matter lesions that are associated with disease progression. We analyze lesions and normal appearing white matter (NAWM) longitudinally (0 and 6 months) and also for progression of disease. We use the expanded disability status scale (EDSS) to assess disease progression. The findings suggest that the high-frequency scale instantaneous amplitude can be used to differentiate between lesions associated with early and advanced disease stages. The classification results using the IF information and support vector machines produced a maximum sensitivity of 0.86, specificity of 0.76 and a maximum correct classification of 0.71. © 2010 IEEE.
Keywords: MRI; Multiple sclerosis; Multiscale AM-FM analysis